Femtosecond laser micromachining of polylactic acid/graphene composites for designing interdigitated microelectrodes for sensor applications. (May 2018) - Paula, Kelly T.; Gaál, Gabriel; Almeida, G.F.B.; Andrade, M.B.; Facure, Murilo H.M.; Correa, Daniel S.; Riul, Antonio; Rodrigues, Varlei; Mendonça, Cleber R.
Highlights: Films produced from conductive graphene/Polylactic acid (PLA) filaments. Femtosecond laser micromachining for patterning composite graphene films. Designing graphene/PLA interdigitated microelectrodes for sensor applications. Abstract: There is an increasing interest in the last years towards electronic applications of graphene-based materials and devices fabricated from patterning techniques, with the ultimate goal of high performance and temporal resolution. Laser micromachining using femtosecond pulses is an attractive methodology to integrate graphene-based materials into functional devices as it allows changes to the focal volume with a submicrometer spatial resolution due to the efficient nonlinear nature of the absorption, yielding rapid prototyping for innovative applications. We present here the patterning of PLA-graphene films spin-coated on a glass substrate using a fs-laser at moderate pulse energies to fabricate interdigitated electrodes having a minimum spatial resolution of 5 μm. Raman spectroscopy of the PLA-graphene films indicated the presence of multilayered graphene fibers. Subsequently, the PLA-graphene films were micromachined using a femtosecond laser oscillator delivering 50-fs pulses and 800 nm, where the pulse energy and scanning speed was varied in order to determine the optimum irradiation parameters (16 nJ and 100 µm/s) to the fabrication of microstructures. The micromachined patterns were characterized by optical microscopy and submitted to electrical measurements in liquid samples, clearly distinguishing all tastes tested. Our results confirm the femtosecond laser micromachining technique as an interesting approach to efficiently pattern PLA-graphene filaments with high precision and minimal mechanical defects, allowing the easy fabrication of interdigitated structures and an alternative method to those produced by conventional photolithography.